Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 348227 species occurrences available in GBIF matching the query: { "or" : [ "TaxonKey is Sparganium hyperboreum Laest. ex Beurl.", "TaxonKey is Andromeda polifolia L.", "TaxonKey is Comptonia asplenifolia", "TaxonKey is Alnus incana Linnaeus, 1753", "TaxonKey is Bidens cernua L.", "TaxonKey is Chenopodium gigantospermum Aellen", "TaxonKey is Ranunculus lapponicus L.", "TaxonKey is Scirpus validus (Boeckeler) Kuntze", "TaxonKey is Pinus funebris Kom.", "TaxonKey is Potentilla palustris (L.) Scop.", "TaxonKey is Triglochin maritimum Linnaeus", "TaxonKey is Ranunculus hyperboreus Rottb.", "TaxonKey is Potamogeton epihydrus Raf.", "TaxonKey is Potamogeton filiformis Pers.", "TaxonKey is Cornus stolonifera Michx.", "TaxonKey is Menyanthes trifoliata L." ] } The dataset includes 348227 records from 546 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0022189-151016162008034/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences